نبی کریم ﷺ کی خارجہ پا لیسی کا عملی جا ئزہ: A practical evaluation of the foreign policy of the Prophetﷺ - Rathore*, Dr. Aman Ullah; Iqbal, Dr. Asim (Al-Amīr Research Journal for Islamic Studies, 2023)
That Islamic foreign policy is guided by the principles of peace, justice and mutual respect, as shown by the Prophet’s treatment of other nations during his time. It established diplomatic relations, signed treaties and engaged in negotiations to resolve disputes and promote understanding. Quranic verses and the Prophet’s actions serve as guidelines for Muslim countries to conduct their foreign affairs in a manner that promotes peace, harmony and cooperation with other nations. Keywords: Foreign policy, Justice, Prophet’s, Diplomatic relations, Muslim countries, Foreign affairs, Harmony, Nations.